'You do it like this!': bare impersonals as indefinite singular generics - Kirkpatrick, J; Knobe, J (Taylor & Francis, 2024)
Sentences with impersonal pronouns, like You do it like this, seem to make both statistical and prescriptive claims, that a certain way of behaving is common and that it is prescriptively good. We argue that these kinds of sentences are closely related to another kind of sentence, namely, indefinite singular generics, like A person does it like this. We propose that there is a single underlying mechanism that allows both kinds of sentences to express mixed statistical/prescriptive readings. We then provide a compositional semantic analysis of these sentences and explain how, together with this single underlying mechanism, it accounts for this phenomenon.